Removal of nutrients and veterinary antibiotics from manure-free piggery wastewater in a packed-bed A/O process at normal atmospheric temperature. Issue 5 (23rd February 2023) - Bao, Hongxu; Liu, Min; Li, Xianhui; Ren, Nanqi; Li, Jianzheng
ABSTRACT: A packed-bed anaerobic-aerobic reactor (PBAOR) with two anaerobic and two aerobic compartments was constructed to treat manure-free piggery wastewater which was characterized by high ammonium (NH4 + -N) and low ratio of chemical oxygen demand (COD) to total nitrogen (TN). Performed for 60 days at the normal atmospheric temperature of 25 °C with a constant hydraulic retention time of 32 h and reflux ratio of 2.0, a stable state in pollutants removal was obtained in the PBAOR. Within the next routine operation process, the removal of COD, NH4 + -N and TN was above 85.7%, 98.2% and 85.8%, with a residual less than 81.7, 7.2 and 39.9 mg L −1 in effluent, respectively. Twelve veterinary antibiotics classified into tetracyclines (TCs), sulphonamides (SAs) and fluoroquinolones (FQs) were detected from the piggery wastewater. The PBAOR was effective in removing TCs and SAs with an average removal of 74.8% and 93.3%, respectively, but presented a negative removal for FQs. Most COD in the piggery wastewater was mainly removed in the first two anaerobic compartments along with an obvious removal of TCs and SAs, while the TN were mainly removed in the last two aerobic compartments with the negative removal of FQs. GRAPHICAL ABSTRACT: UF0001